AKTIVITAS ANTIBAKTERI NBENZOILAMOKSISILIN DAN N34DIKLOROBENZOILAMOKSISILIN TERHADAP Staphylococcus ATCC 25923 DAN Escherichia coli ATCC 35218 - Harry Santosa; Bambang Soekardjo; Ami Soewandi J S (The East Java Biological Society, 2000)
N-Benzolamoxicillin and N-3,4-dichlorobenzolamoxicillin were synthesized from amoxicillin by acylation with benzoylchloride and 3,4-dichlorobenzoylchloride respectively. Structure characterization of the amoxicillin derivative compounds were done by UV, IR and 1H-NMR spectroscopy. Both derivative compound has antibacterial antivity against Staphylococcus aureus and Escherichia coli. The activity of N-3,4-dichlorobenzolamoxicillin is more active than N-Benzolamoxicillin.